Analisis Korelasi Antara Kesejahteraan Ekonomi dan Keamanan Nasional Dalam Konteks Strategi Nasional - Imam Ghozali; Vicky Chandra; Faiza Ayrul; Indah Rachma; Niken Ayu; Amelia Nur (Journal Economic Excellence Ibnu Sina, 2024)
In recent decades, countries have faced significant challenges involving economic instability and increasingly complex security threats. Threats to security can disrupt economic activity, and trigger instability that inhibits economic growth and vice versa. This research aims to analyze the reciprocal relationship between economic well-being and national security in the context of national strategy. Through a literature study approach, this research collects and analyzes relevant sources on economic welfare, national security, and the context of national strategy. The results of this study reveal that increased economic prosperity can also improve people's welfare, thereby strengthening national security. Likewise, secure national security can enable more stable and sustainable economic development. Therefore, there is a need for policies that are integrated with national strategies, such as policies with security strategies, policies with economic strategies, and policies with welfare strategies to ensure the realization of national interests.